The Relationship between Antenatal Care Quality and Pregnancy Outcomes: Systematic Literature Review - Panjarwanto, Dwi Andhika; Restalia, Fianda; Indrawan, I Wayan Agung; Utomo, Rudi Priyo; Permana, Adin Yan (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
This study investigates the correlation between the quality of prenatal care and pregnancy outcomes through a comprehensive literature review. The systematic literature review aims to elucidate the relationship between prenatal care quality and pregnancy outcomes while identifying key factors influencing care quality. Relevant studies were identified through an extensive search of databases, including Google Scholar, ScienceDirect, and PubMed, using specific keywords related to antenatal care quality, serum levels, and pregnancy outcomes. Articles published within the last ten years were screened based on inclusion criteria, resulting in 12 original studies selected for detailed analysis. The findings reveal a statistically significant correlation between prenatal care quality and pregnancy outcomes. Inadequate prenatal care was associated with a higher risk of preterm birth, low birth weight, and complications during delivery. Socioeconomic factors such as income level, education, and access to healthcare services were identified as critical determinants of prenatal care quality. This study highlights the urgent need to enhance the accessibility, continuity, and quality of prenatal care to reduce maternal and neonatal mortality and morbidity, particularly in resource-limited settings. Policy implications suggest the necessity of targeted interventions to address disparities in prenatal care, including improving healthcare infrastructure, training healthcare providers, and implementing community-based programs. In conclusion, the study underscores the pivotal role of high-quality antenatal care in ensuring favorable pregnancy outcomes. Tackling socioeconomic barriers and enhancing service delivery are crucial to reducing adverse outcomes and promoting maternal and child health. The findings call for policy reforms to strengthen antenatal care services, especially in underserved regions, to achieve better health outcomes for mothers and infants.